Intercropping alfalfa with select grass species for increased yield and quality under deficit irrigation - Doyle, Hunter, author; Brummer, Joe, advisor; Cabot, Perry, committee member; Ippolito, Jim, committee member (Colorado State University. Libraries, 2023)
Drought and water scarcity have plagued the Western US for decades. As these issues become more prevalent, we must explore possibilities to utilize available water more efficiently. The objective of this study was to: Evaluate the ability of mixed and stripped intercropping alfalfa with grasses to increase yield and quality of the forage produced under deficit irrigation. Alfalfa (Medicago sativa) is the most common forage grown in the West and is known for its high-water use. Intercropping alfalfa with perennial grasses can potentially improve water use efficiency. Orchardgrass (Dactylis glomerata), meadow brome (Bromus biebersteinii), and tall fescue (Festuca arundinacea) were mixed on the same bed or strip intercropped on alternating beds with alfalfa under 100% and 60% ET irrigation regimes using subsurface drip irrigation. Three cuts occurred in 2021 and 2022, with deficit irrigation starting after cut one. Yield, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), neutral detergent fiber digestibility (NDFD), and relative feed value (RFV) were analyzed in this study. During year one, irrigation did not have a significant impact on yield due to high precipitation and the fact that alfalfa performs well under deficit irrigation. Quality was not affected by irrigation treatments throughout both years of this study. Planting treatments significantly impacted yield and all quality parameters throughout this study. In 2021, mixed intercropping treatments averaged 14,210 kg ha-1, stripped treatments averaged 12,285 kg ha-1, and alfalfa averaged 13,406 kg ha-1; significant differences were not present. All mixed treatments, tall fescue stripped, and meadow brome stripped yields were similar to alfalfa in 2021. In 2021, quality was generally only reduced in mixed intercropping treatments compared to alfalfa in the first cutting. The inclusion of grasses with alfalfa reduced crude protein content and increased neutral detergent fiber content during cutting one, overall reducing quality. In cuttings two and three, mixed intercropping did not generally reduce quality. Stripped treatments also reduced quality in cutting one but did not have a large effect on quality in subsequent cuttings. Relative feed value, a common parameter used among producers, was similar among all treatments for all cuttings in 2021. In 2022, deficit irrigation had a significant impact on yield in cuttings two and three. Yields due to deficit irrigation were reduced by 22% and 35% in cuttings two and three, respectively. Total yearly yields were reduced by 12.5% between irrigation treatments. Total yields in mixed intercropping treatments were significantly higher than the alfalfa monoculture, especially the tall fescue and orchardgrass. Meadow brome generally had a higher yield than alfalfa, though not always significant. Mixed treatments averaged 13,308 kg ha-1 and stripped treatments averaged 9,488 kg ha-1 compared to alfalfa at 10,758 kg ha-1. Similar to 2021, quality was only reduced in intercropping treatments during the first cutting. Crude protein and RFV decreased while NDF and ADF increased in intercropping treatments compared to alfalfa alone, resulting in reduced quality. In subsequent cuttings, quality was generally similar among intercropping treatments and alfalfa alone. Mixed intercropping demonstrated to be more productive throughout both years of this study compared to stripped intercropping. Advantages from intercropping were reduced in stripped treatments due to independent cultivation and limited species interactions. Grass species did not have as large of an effect on yield and quality compared to intercropping method. Tall fescue typically performed the best of the grasses, yet all grasses in mixed intercropping performed well compared to alfalfa. Mixed intercropping grass with alfalfa can lead to increased yields with minimal effects on forage quality compared to alfalfa alone. As severe drought continues in areas across the Western US, mixed intercropping could be an option for maintaining or improving yields while producing similar forage quality compared to alfalfa alone under deficit irrigation.
Keywords: cool-season grasses; hay; alfalfa; intercropping; forage